ACE I/D polymorphism is a risk factor of Alzheimer's disease but not of vascular dementia - Kölsch, Heike; Jessen, F.; Freymann, N.; Kreis, Markus; Hentschel, Frank; Maier, W.; Heun, R. (Neuroscience letters, 2005)
Different studies have investigated the effect of the angiotensin converting enzyme (ACE) insertion/deletion (I/D) polymorphism on the risk of Alzheimer dementia (AD). However, results on the association of the ACE-I allele with AD have been inconclusive. A recent meta-analysis reported an association of the I-allele with the risk of AD. A few small studies also investigated the effect of ACE polymorphism on the risk of vascular dementia (VD). We have investigated the effect of ACE I/D polymorphism in 351 AD and 155 VD patients and 348 healthy controls. We found the I/I genotype to be associated with an increased risk of AD, but not with the risk of VD. Cell-specific effects of ACE polymorphism are suggested, additional studies on neuronal cells might help to understand the role of this polymorphism in AD.
Available online 10 December 2004
Gesehen am 10.11.2020